Digital Competencies of Pre-Service Teachers in Indonesia: Are They Qualified for Digital Education? - Rahim, Fanny Rahmatina; Widodo, Ari; Suhandi, Andi; Ha, Minsu (Indonesian Journal of Educational Research and Review, 2023)
In order to organise, carry out, and evaluate improved learning processes, education currently demands that prospective teachers have digital capabilities. However, there is still a lack of research that comprehensively examines, within the framework of digital education, the digital competences of prospective teacher students in Indonesia, particularly for those specialising in Physics teaching. The purpose of this article is to assess Indonesian prospective teacher students' digital literacy within the framework of digital education. The study's methodology is quantitative. A survey method was used to collect data from students and alumni of the Physics Education program from 2017 to 2022. A total of 248 respondents participated in the study, including 202 students and 46 alumni. The collected data were then analyzed quantitatively. The research findings indicate that the majority of respondents showed a positive response to their abilities in all assessed dimensions of digital competencies. Literacy in information and data, communication and collaboration, digital content creation, safety, and problem-solving received favourable ratings. However, there is potential to improve skills in digital content creation. Overall, the respondents demonstrated a good level of competence in the evaluated digital competency indicators. The data also revealed that students and alumni of the Physics Education program are accustomed to using technology in their academic activities. They utilize Learning Management Systems (LMS) to access course materials, submit assignments, and take exams. Additionally, they employ various applications and collaborate online in groups. The program also offers courses that support the use of technology in learning.